Multi-Microgrid System Optimization Scheduling Including Electric Vehicle Coordinated Charging and Reward and Punishment Ladder Carbon Trading - GAO Ya, XU Yanchun, ZHANG Tao, SONG Wenyu, WANG Ping, XI Lei, MI Lu (Dianli jianshe)
To further reduce the carbon emission of the microgrid system under the background of “dual carbon，” a low-carbon operation strategy of multi-microgrid integrated energy system is proposed，which accounts for the coordinated charging of electric vehicles （EVs） and the “reward and punishment”-type stepped carbon-trading mechanism. First，a dynamic urgency index （DUI） is proposed to reflect the charging demand of the user and a coordinated EV-charging model is established to minimize the peak-to-valley difference of the total electric load in the microgrid. Subsequently，a two-stage power-to-gas （P2G），distributed generation （DG） and combined heat and power unit （CHP） cooperative operation model is constructed. Finally，considering the electrothermal interactions in the multi-microgrid integrated energy system，a ladder-type carbon-price mechanism with reward and punishment （LCPMRP） is implemented to constrain the carbon emission of the system，thus further improving the low-carbon economy of the system. Simulation results show that the LCPMRP can improve the low-carbon economic operation of the system when considering the interaction between electric energy and heat energy in a multi-microgrid. The proposed DUI is used to schedule EVs，which satisfies the charging demand of EV owners and reduces the peak-valley difference of the total electric load in the microgrid. The introduction of the two-stage P2G，DG，and CHP cooperative operation model reduces carbon emission in the microgrid and weakens the thermoelectric coupling relationship of the CHP system.